Co-diffused bi-facial PERT solar cells. (September 2017) - Fellmeth, Tobias; Meier, Sebastian; Clement, Florian; Wolf, Andreas; Knauss, Holger; Havercamp, Helge
Abstract: The authors present a fully solderable, co-diffused and bi-facial PERT solar cell where the rear BSG/SiN stack acting both as dopant and passivation source reaching a mean efficiency of 20.4 %. The conductivity induced by the presence of the p + layer at the rear reduces series resistance losses significantly by simultaneously enabling the use of lowly doped Si wafers that reduce B-O degradation while maintaining a high fill factor. Parallel processed, mono-facial pendants reach the same efficiency level. A higher FF for the mono-facials is compensated by a higher Voc for the bi-facial PERT devices. SEM analysis on test structures show an overall superior, local Al-Si contact in terms of voiding and BSF thickness with reducing printed finger width. At reverse bias, the "conventional process" shows a typical behaviour for such architecture of elevated current flow around the edges. For the "adapted process" up to -12 V, the authors demonstrate a virtually shunt-free device exhibiting reverse currents far below 1 A with no additional process step.